A Proposed Model for Identification of Childhood Apraxia of Speech in Young Children. - Pukonen, Margit; Grover, Lisa; Earle, Cindy; Gaines, Robin; Theoret-Douglas, Carol (Canadian Journal of Speech-Language Pathology & Audiology)
Clinicians may suspect Childhood Apraxia of Speech (CAS) in young children whose verbal expression is significantly below their receptive abilities. However, there are no definitive diagnostic markers for CAS and there is an overlap of symptoms between children with CAS, other types of Speech Sound Disorders, and children who are Late Talkers. The purpose of this article is to describe a decision-making process based on Response to Intervention principles for identifying and providing intervention to young children with severe speech sound disorders. It provides clinicians with guidelines for selecting developmentally appropriate interventions as well as indicators to monitor over the course of intervention when CAS is suspected. Differential diagnosis and identification of CAS are based on the quality and quantity of change in the child's overall communication profile in response to intervention as well as the presence of specific indicators that are associated with CAS.